The Role of the Pancasila Ideological Development Agency in Regulation Development and Regulatory Harmonization - Purwanti, Ani; Putri, Fayreizqi Azellea Mashanda; Mahfud, Muh. Afif (Jurnal Politik Indonesia: Indonesian Political Science Review, 2022)
The Pancasila Ideology Development Agency or BPIP was formed due to the urgency of creating a state apparatus that functions to maintain the application of Pancasila values in the life of the nation and state. BPIP also acts to formulate an outline of the Pancasila ideology, coordinate, synchronize, advocate, monitor, evaluate, recommend, develop and control strategic policies and regulations for development. Of the many tasks and functions of BPIP, this article discusses one of the functions, namely regulatory oversight. This regulatory oversight function aims to monitor, evaluate, and harmonize regional and central regulations. They are in line with Pancasila's values inclusive, democratic, and socially just. Regulatory oversight is carried out by the Deputy for Legal Affairs, Advocacy, and Regulatory Oversight. The strategic aspect of the Deputy for Law, Advocacy and Regulatory Oversight, in this case, is the implementation of an effective and efficient program in implementing Pancasila Ideology Development through the internalization and institutionalization of Pancasila in the field of law, advocacy, and regulatory oversight. Based on the research, the contribution of this deputy is the availability of the Pancasila values indicator design, the implementation of quality analysis and synchronization, the performance of advocacy for the development of the Pancasila ideology, and the implementation of the effective internalization and institutionalization of Pancasila. Through this deputy, BPIP is then expected to make a positive contribution to increasing the harmonization of regulations on Pancasila to realize social inclusion, institutionalizing Pancasila, and mainstreaming the ideals of Pancasila.